Farklı şekil ve büyüklükteki kokristallerin morötesigörünür bölge (UV/VİS) spektroskopisi ile çözünme konsantrasyonunun analizi - Elmas, Sinem (Fen Bilimleri Enstitüsü, 2020)
Sedef hastalığı Dünya nüfusunun yaklaşık olarak %2'sinde görülen bulaşıcı olmayan bir hastalıktır. En yaygın nedeni genetik faktörler olan bu hastalık çevresel ve psikolojik olaylar ile tetiklenmektedir. Hastalık kısa süreli görülebileceği gibi ömür boyunca da devam edebilmektedir. Hastalık genellikle topikal tedavilerle (krem, merhem) kontrol edilmeye çalışılsa da yetersiz kalınan durumlarda sistemik tedaviye ihtiyaç duyulmaktadır. Hastalığın tedavisinde kullanılan aktif farmasötik bileşen (AFB), düşük çözünürlüğe sahip olan immün sistemin yanıt düzenlemesinde yer alan hücreler için bir inhibitördür. Su içindeki çözünürlüğü düşük olan AFB'lerin çözünürlüğünü artırmak için birçok yaklaşım mevcuttur. Partikül boyutunu küçültme, tuz oluşumu, hidrat ve solvat oluşumu, kokristaller bu yaklaşımlardan bir kaçıdır. Bu yöntemlerden biri olan kokristalizasyon yöntemi ile bileşenlerinden biri AFB olan homojen kristal malzemeler oluşturulabilmektedir. Kokristalizasyon ile aktif maddenin sadece çözünürlüğünü değil, çözünme profili, stabilite, biyoyararlanım gibi önemli fizikokimyasal özelliklerini de geliştirmek mümkündür. Kokristallerde çözünme analizinin yapılması biyoyarlanım performansının tahmini ve ileriki analiz aşamaları iyi bir ön çalışma olduğu için önemlidir. Nihai katı dozaj formunda yardımcı maddelerin kullanılması aktif maddenin dozajında sınırlayıcı olabilmektedir. Kokristallerin büyüklük, şekil gibi fiziksel özellikleri bu gibi durumlarda oldukça önemli olmaktadır ve ürün geliştirme sırasında kokristallerin çözünme performansının değerlendirilmesi önem taşımaktadır. Büyümekte olan kokristalin şekline ve büyüklüğüne kokristalizasyon sırasında kullanılan karıştırıcının tipi, karıştırma hızı, kullanılan çözücü ve katkılar, soğutma hızı vb. faktörler etki etmektedir. Farklı şekil ve büyüklükteki kokristallerin çözünmesi de farklı olmaktadır. Kristallerin özellikleri dışında çözücü ortamı da kokristallerin çözünme profilini etkilemektedir. Ortam sıcaklığı, çözücünün pH derecesi, çözünmeyi artırmak için katkı maddelerinin kullanılması vb. durumlardan çözünme profili etkilenmektedir. Bu çalışmada farklı şekil ve büyüklüklere sahip olan kokristaller için çözünme çalışması yapılmıştır. Kullanılan kokristal sedef hastalığının tedavisinden kullanılan bir AFB ve benzoik asit (BA) koformerden oluşmaktadır. AFB/BA molar olarak 2/1'dir. Mide sıvısı ortamına benzer çözücü koşulu yaratılması hedeflenerek asidik pH derecesinde bir çözücü ortamı hazırlanmış ve her deneme için aynı ortam şartları altında çözünme çalışması yapılmıştır. Öğütme işlemi ilaç endüstrisinde partikül boyutunu küçültmek ya da istenilen boyutta partikül elde etmek için sıklıkla başvurulan bir yöntemdir. Kokristal örneklerinden birine öğütme işlemi yapılarak, öğütme sonucu çözünme konsantrasyonunun nasıl değiştiği incelenmiştir. Kokristalin çözünme konsantrasyonu öğütme işlemi öncesi ve sonrası için aynı kristal büyüklüklerinde karşılaştırılarak değerlendirilmiştir. 5., 10., 20., 30., 45., 60. ve 120. dakikalarda çözeltiden alınan örneklerin morötesi-görünür bölge (UV/Vis) spektroskopisi ile 190-500 nanometre (nm) dalga boyu aralığında absorbans değerleri ölçülmüştür. Aktif bileşen 290-390 nm, benzoik asit ise 200-280 nm dalga boyu aralığında absorblanmaktadır. Aktif bileşenin çözünmenin herhangi bir anındaki konsantrasyonunu hesaplamak için bir kalibrasyon eğrisi hazırlanmıştır. Kalibrasyon eğrisi, bir maddenin bir çözelti içindeki bilinmeyen konsantrasyonunu belirlemek için kullanılan bir yöntemdir. Bilinen konsantrasyonlarda kokristal çözeltileri hazırlanarak absorbans değerleri ölçülmüştür ve bu değerlere karşılık bir eğri çizilerek kalibrasyon eğrisi hazırlanmıştır. Kalibrasyon eğrisinin korelasyon kat sayısı (r2) = 0,9999 olarak bulunmuştur. Kokristallerin büyüklüğünün küçülmesi ile çözünme konsantrasyonunun arttığı gözlemlenmiştir. Kristal büyüklüğü dağılımının geniş olduğu (25-200 µm) örneklerde kristal büyüklüğü dağılımının 100-200 µm, 50-100 µm ve 25-50 µm aralıklarında sınırlandırılması çözünmeyi artırmıştır. Aynı kristal büyüklüğü aralığında olan kokristal örneklerinin çözünmeleri karşılaştırıldığında ise öğütme işlemi yapılan kokristal örneğinin çözünme konsantrasyonunun en fazla olduğu gözlemlenmiştir. Ayrıca kokristal yüzeyinin pürüzsüz ve az çıkıntılı olması durumunda çözünme konsantrasyonunun arttığı gözlemlenmiştir. Yüzeyinde fazla çıkıntıları olan küme şeklindeki kokristal örneğinin çözünme konsantrasyonu tüm kristal büyüklükleri aralıklarında pürüzsüz yüzeyi olan bipiramit şeklindeki kokristalin çözünme konsantrasyonundan daha az olmuştur. Biyoyararlanım çalışmalarının, bu çalışma sonuçlarını desteklemesi durumunda kokristallerden çözünme konsantrasyonu fazla olan kokristal formunun ilaç formülasyonunda kullanılması ve aktif maddenin dozajının azaltarak tedaviye devam edilmesi vaat edilmektedir.

Psoriasis is an itchy skin disease where white, thick and dry dandruff is observed on a red-pink colored. This disease occurs in about 2% of the world's population. The probability of seeing the disease at any age and gender is equal. In some individuals, the disease duration may take several months, or it may reoccur at different times throughout life. The most common reason for psoriasis is genetic factors. Besides the genetic factors, it can cause disease to be triggered in environmental and psychological events. Some studies have observed that 30% of individuals diagnosed with psoriasis have become a type of psoriatic arthritis. In this type of psoriasis, severe pain and swelling are observed in the joints. Treatment of psoriasis and psoriatic arthritis depends mostly on the current state of the disease. Mild disease is treated with topical therapies. Further, with the increasing severity of the disease, topical therapies might be combined with phototherapy. Systemic treatments are used in the long-term treatment of the disease. The active pharmaceutical ingredient (API) used in the treatment of the disease is an inhibitor for cells involved in the response regulation of the immune system. APIs are generally used in formulation in crystal form, where they are thermodynamically the most stable form. APIs have very low solubility and there are many approaches to increase solubility. There are many approaches to increase solubility. Micronization (particle size reduction), salt formation, emulsification, use of co-solvents are some of these approaches. In recent years, cocrystals have emerged as a possible solution to poor solubility. Cocrystals are structurally homogeneous crystal materials containing two or more components found in certain stoichiometric ratios. The components in the cocrystal interact with non-covalent bonds (Van der Waals, hydrogen bond, etc.). These interactions result in crystal structure with improved chemical and physical properties (e.g. solubility, melting point, mechanical properties, stability, hydration) compared to individual solid components. It is very important whether cocrystals have targeted properties, characterizing its physical and chemical properties, choosing the thermodynamically most durable form of the active ingredient, controlling the crystal shape, size and distribution. In this way, a possible problem that may affect production in the early stages of drug development can be prevented. While the basic physicochemical properties of cocrystals are analyzed by powder X-ray diffraction, single-crystal X-ray diffraction, infrared spectroscopy, raman spectroscopy, differential scanning calorimetry, high-performance liquid chromatography, and ultraviolet-visible (UV/Vis) spectroscopy, surface properties, and crystal sizes can be analyzed by scanning electron microscope. Dissolution behavior is an important characterization stage for evaluating the crystal, understanding the dissolution mechanism and predicting the bioavailability of the drug. It is mentioned in the literature that the data obtained in dissolution studies are a good indicator of the drugs in vivo performance. The dissolution of cocrystals of different shapes and sizes is also different. Apart from the properties of the crystals, the solvent environment also affects the dissolution profile of the cocrystals. Dissolution is affected by situations like ambient temperature, pH of solvent, use of surfactant to increase dissolution, etc. The shape and size of the growing cocrystal changes with the stirrer, solvent, and additives used during crystallization. In this study, dissolution study was carried out for cocrystals of different shapes and sizes. Cocrystal contains an API used in the treatment of psoriasis and a benzoic acid (BA) coformer. An acidic solvent environment similar to the pH level of the gastric fluid was prepared. For each experiment 500 ml, acidic solution and 7,5 mg cocrystals were used. It was stirred at a temperature of 37 °C at 300 rpm in a magnetic stirrer. Dissolution study was carried out under the same ambient conditions for each experiment. Every 5, 10, 20, 30, 45, 60 and 120 minutes 2 ml of samples were collected from the solution with a pipette. Samples were measured with ultraviolet-visible (UV/Vis) spectroscopy in the 190-500 nanometer (nm) wavelength. The API absorbs in the wavelength range of 290-390 nm and benzoic acid absorbs in the range of 200-280 nm. A calibration curve was prepared to determine the concentration of the active ingredient at the moment of dissolution using the absorbance value. In the calibration curve method, firstly standard solutions of the substance are prepared at known concentrations. Maximum cocrystal concentration value is taken as 0.0152 mg/ml and 8 solutions with different concentrations in decreasing value were prepared with a cocrystal. To ensure that the cocrystals dissolve completely, the mouth of the glass beakers were closed with parafilm and stirred on a magnetic stirrer at 37 °C for 24 hours at 300 rpm. Then absorbance value of API obtained for each solution. A curve was drawn using known concentration values and absorbance values obtained from UV / Vis measurements. Correlation coefficient (r2) of the curve was found as 0,9999. The maximum absorbance value and dissolution concentration of the active ingredient absorbed at the wavelength of 290-390 nm was calculated using the calibration curve. Milling is a frequently used method in the pharmaceutical industry to reduce the particle size or to obtain the desired size particle. Milling was done to one of the cocrystal samples and how the dissolution concentration changed evaluated. It has been observed that the concentration of dissolution increases with the reduction of the size of the cocrystals. In samples with large crystal size distribution, the particle size distribution limited between the sizes 100-200 µm, 50-100 µm and 25-50 µm. It was observed that the concentration of dissolution increased by limiting the cocrystal size distribution. Milled cocrystal sample dissolution concentration in the crystal size range of 25-50 µm has reached the 0,0187 mg/ml which was the highest dissolution concentration among all cocrystal samples after 120 minutes. This concentration value is higher than the dissolution concentration of bipyramid and clump shaped cocrystals that containing particles smaller than 25 µm. It shows that milling process not only reduces the particle size but also increases the surface area. When the dissolution of the cocrystal samples in the same crystal size distribution range (50-100 µm) was compared it was observed that the dissolution concentration of the that applied on milling was the highest. This is an expected result due to the increased surface area. Also, it has been observed that the dissolution concentration increases if the cocrystal surface is smooth and less protruding. Dissolution concentration of clump shaped cocrystal with excess protrusions on the surface, was lower than bipyramid shaped cocrystal in all particle size range. If in vivo studies support the results of this study, it is promised to use the form with high dissolution concentration from the cocrystals in the drug formulation and continue the treatment by reducing the dosage of the API.
Analysis of the dissolution concentration of different shape and size cocrystals with ultraviolet-visible (UV/VIS) spectroscopy
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: fiziksel özellikler; physical properties; kokristaller; cocrystals; morüstü-görünür spektroskopisi